Ртуть в углях Сибири - Волостнов А. В. Александр Валерьевич; Арбузов С. И. Сергей Иванович; Осипова Н. А. Нина Александровна; Ильенок С. С. Сергей Сергеевич; Купреева Н. В. (2010, 2010)
В фонде НТБ ТПУ отсутствует